2016
DOI: 10.1103/physrevd.93.054036
|View full text |Cite
|
Sign up to set email alerts
|

Long range azimuthal correlations of multiple gluons in gluon saturation limit

Abstract: We calculate the inclusive gluon correlation function for arbitrary number of gluons with full rapidity and transverse momentum dependence for the initial glasma state of the p-p, p-A and A-A collisions. The formula we derive via superdiagrams generates cumulants for any number of gluons. Higher order cumulants contain information on correlations between multiple gluons, and they are necessary for calculations of higher dimensional ridges as well as flow coefficients from multi-particle correlations. * ozonder… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…[ [29][30][31], we suggested that investigating the three-hadron correlations could rule out one of the two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[ [29][30][31], we suggested that investigating the three-hadron correlations could rule out one of the two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [38], we derived the formula for the n-gluon correlation function C n with full momentum and rapidity dependence by using the glasma superdiagrams we developed. Here we quote the formulas that we will use in the next section to derive five-and six-gluon correlation functions.…”
Section: Formula Of N-gluon Correlation Functionmentioning
confidence: 99%
“…4 The formulas for N 1,2 given in Ref. [38] included a typo and missed the prefactor f n , and the prefactor in the second brackets mistakenly read 2 h instead of 2h. These mistakes in Ref.…”
Section: Formula Of N-gluon Correlation Functionmentioning
confidence: 99%
See 2 more Smart Citations